Towards a strategy for project management implementation - Chris J. Brown (South African Journal of Business Management, 1999)
The basic tenet of this article is that the implementation of project management as a way of managing, in formerly functionally structured organisations, is a complex process requiring strategic management intervention. The three outstanding Issues contributing to this complexity are expounded. These are differing characteristics of the range of an organisation's projects that must be provided for: the inherent characteristics of functional organisations inhibiting to a cross-functional approach that need to be overcome: and the very necessary mind shift to the project management culture that needs to be instilled. The ground rules for project management implementation is laid down by way of eight questions that must be answered on top management level. These resolve around a firm commitment to the replacement of old, seemingly well proven practices as well as around the implications and consequences for the organisations. The article then proceeds with proposing framework for the process of project management and implementation. This is presented in seven steps, concluding that the implementation should be approached as a project in own right. To that effect a generic work breakdown structure is offered as a guideline.
Keywords: 650